Nursing biocrusts: isolation, cultivation, and fitness test of indigenous cyanobacteria. Issue 4 (29th January 2019) - Giraldo‐Silva, Ana; Nelson, Corey; Barger, Nichole N.; Garcia‐Pichel, Ferran
Abstract : Biological soil crusts (biocrust) are microbial communities that develop at the soil surface of drylands and play an important role in erosion control and fertility. Soil surface disturbance from a broad range of natural and human processes (e.g. fire, livestock grazing, off‐road traffic) cause significant losses in biocrust cover and associated ecosystems services. Hence, biocrust restoration is emerging as an important intervention strategy to rehabilitate degraded dryland soils. In a multistep process, we designed protocols for the establishment of "microbial nurseries" to produce photosynthetic cyanobacterial inoculum for biocrust seeding at scale. We first report on the strategy for isolation, directly from the target site, of a large culture collection of cyanobacteria that included multiple representatives of the five most common biocrust taxa. After genetic pedigreeing of these isolates, we could select those that best matched field populations genetically for scale‐up cultivation. We then developed protocols for effective cyanobacterial biomass production to obtain sufficient inoculum. This was followed by conditioning treatments (hardening off) to preacclimate this inoculum to the stressful conditions expected in the field. Finally, we show that the inoculum obtained was fit to thrive in its original soil under natural outdoor conditions if sufficient water was available. We repeated this process successfully for four sites, two in the hot Chihuanuan desert and two in the cooler Great Basin Desert, and on two textural types of soils in each. The cyanobacterial biocrust nursery approach represents a versatile, viable, and safe tool for the rehabilitation of dryland soils.